Implementasi Kearifan Lokal Banyumas Bidang Sosial pada Generasi Milenial di Era Global - Taufiq, Muhammad; Hartini, Sri; M, Munasib (Madani: Jurnal Ilmiah Multidisiplin, 2025)
With the advancement of technology in the global era, it has created an easy and instant lifestyle for the millennial generation. However, this lifestyle can evolve into a consumptive one that hurts the social and economic values of the Indonesian nation. In order not to lead to negative things, the millennial generation must not forget the cultural roots (local wisdom) that already exist because in it there are noble values that must be preserved, in addition to continuing to enjoy modern culture. This study was conducted to explore, understand, and further examine the application of Banyumas local wisdom in the current era of globalization. A qualitative descriptive methodology was employed in this study. This study succeeded in finding the characteristics of Banyumas local wisdom in the social field in the form of cablaka/blakasutha/thokmelong, ngapak language, and rembugan. The implementation of Banyumas local wisdom in the social field is carried out by applying the philosophy of cablaka, rembugan, and the egalitarian values of ngapak language for the millennial generation in the global era.